Social commerce: how should portuguese companies invest in it? - Macedo, André Neto Rodeia (2014)
The massification and globalization of the internet and social media democratized the access to information and changed behaviours and consumption habits. In this context, this thesis pretends to evaluate the impact and degree of acceptance of social commerce in Portugal, by focusing on a sample of 521 consumers who were surveyed through an online survey administered via internet, to which they voluntarily responded. The majority of the surveyed was male young adults, working for others and with a monthly income higher than 1,000€. Since social commerce is still in its infancy stage, there is a huge potential for growth and expansion, and therefore, Portuguese companies should take it in consideration in their future marketing plans and strategies. One of the main findings of this study was that the habit of using daily social networks does not seem to be much valued at the time of the purchase decision, as the great majority of those surveyed affirmed that they never bought anything with direct influence of social networks or directly through these. Furthermore, after publishing a post on the social networks expressing interest or doubts about a brand, most respondents admitted to be fully open to be addressed by a responsible or manager of that brand for customer care purposes. Additionally, about one third of the respondents confessed to have already bought or would like to purchase products or services directly from an online store on Facebook.